2021
DOI: 10.31349/revmexfise.19.010207
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Physics Learning Based on Traditional Games in Senior High Schools during the Covid-19 Pandemic

Abstract: Physics learning during the Covid-19 pandemic must still be done so that students can still get physics intake. This phenomenological research aims to explore physics teacher strategies in conducting traditional game-based learning in senior high schools during the Covid-19 pandemic. The research data was collected through in-depth interviews with 10 physics teachers from five senior high schools in Yogyakarta. The ten participants were taken using the purposive sampling technique. The data analysis used analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Then the results of previous research found that traditional game-based physics learning was carried out using contextual, inquiry, project and problem-based learning models [32]. Previous research also found that the game-based learning group had the best performance among the three groups, followed by the educational video group, and the conventional learning group with the worst performance [33], [34].…”
Section: Introductionmentioning
confidence: 95%
“…Then the results of previous research found that traditional game-based physics learning was carried out using contextual, inquiry, project and problem-based learning models [32]. Previous research also found that the game-based learning group had the best performance among the three groups, followed by the educational video group, and the conventional learning group with the worst performance [33], [34].…”
Section: Introductionmentioning
confidence: 95%
“…In this similar study, teachers were also encouraged to design and develop other game-based activities related to light and sound concepts and include them in their lessons. In the study of Putranta et al, (2021), the integration of traditional game-based physics learning was found to be effective because of the contextual learning and problembased learning models that support and maximize their abilities widely. In the study of Kuo et al, (2023), it was found that in all groups of students, game-based learning and scaffolding perceived similar levels of engagement, engrossment, and total immersion.…”
Section: Problemmentioning
confidence: 99%
“…Teachers can evaluate directly during the game. This method makes learning more lively and dynamic and fosters a sense of comfort, fun, and enthusiasm in students while learning (Daud et al, 2021;Khoirani et al, 2021;Putranta et al, 2021;Pratama & Waskitoningtyas, 2020).…”
Section: Increase Student Activitymentioning
confidence: 99%